1996
DOI: 10.1074/jbc.271.20.12049
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated Protein Kinase in Neutrophils and Enucleate Neutrophil Cytoplasts

Abstract: We employed neutrophils and enucleate neutrophil cytoplasts to study the activation of the mitogen-activated protein kinases (MAPKs) p44 erk1 and p42 erk2 in neutrophils by inflammatory agonists that engage G protein-linked receptors. Formyl-methionyl-leucylphenylalanine (FMLP) rapidly and transiently activated MAPK in neutrophils and cytoplasts, consistent with a role in signaling for neutrophil functions. FMLP stimulated p21 ras activation in neutrophils and Raf-1 translocation from cytosol to plasma membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
63
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 42 publications
11
63
2
Order By: Relevance
“…Tyrosine kinases (mainly Lyn of the Srk-family) (Berton, 1999a;Ptasznik et al, 1996;Welch and Maridonneau-Parini, 1997) and the GTP-binding protein Ras (Worthen et al, 1994) are also activated. Ras activation triggers the MAPK/ERK cascade, which appears to be involved in various chemoattractant-induced neutrophil functions (Krump et al, 1997;Nick et al, 1997;Pillinger et al, 1996). Activation of small GTP-binding proteins of the Ras, Rac, and Rho families regulate actin-dependent processes such as membrane ruffling, formation of filopodia and stress fibers, mediating cell adhesion and motility (Benard et al, 1999;Cox et al, 1997;Nobes and Hall, 1999).…”
Section: Migration Within Interstitial Tissuesmentioning
confidence: 99%
“…Tyrosine kinases (mainly Lyn of the Srk-family) (Berton, 1999a;Ptasznik et al, 1996;Welch and Maridonneau-Parini, 1997) and the GTP-binding protein Ras (Worthen et al, 1994) are also activated. Ras activation triggers the MAPK/ERK cascade, which appears to be involved in various chemoattractant-induced neutrophil functions (Krump et al, 1997;Nick et al, 1997;Pillinger et al, 1996). Activation of small GTP-binding proteins of the Ras, Rac, and Rho families regulate actin-dependent processes such as membrane ruffling, formation of filopodia and stress fibers, mediating cell adhesion and motility (Benard et al, 1999;Cox et al, 1997;Nobes and Hall, 1999).…”
Section: Migration Within Interstitial Tissuesmentioning
confidence: 99%
“…There is also evidence that IL-8 stimulates phospholipase D activity (27), phosphatidylinositol-3 kinase (PI3K) activity (28), and GTP loading of RhoA (29) in human neutrophils. IL-8 has been shown to activate mitogen-activated protein kinase (MAPK) in human neutrophils as well as in enucleate neutrophil cytoplasts (28,30,31). In addition, IL-8 has been shown to stimulate GTP loading of Ras and Raf activation in human neutrophils with a time course that indicates that these events are upstream of MAPK activation.…”
mentioning
confidence: 99%
“…However, ERK may also be activated in response to proinflammatory stimuli (22,23). For example, Vilcek and colleagues (24 -26) have demonstrated that in FS-4 fibroblasts, ERK undergoes activation in response to the cytokines IL-1␀ and TNF-␣, both of which are critical to the pathogenesis of RA.…”
mentioning
confidence: 99%